Research on the Relationship between Jiannan West Jiedushi and Buddhism in the Mid to Late Tang Dynasty (Journal of Advanced Research in Social Sciences, 2024)
This article comprehensively explores the relationship between Xichuan Jiedushi and Buddhism during the mid to late Tang Dynasty through a comprehensive investigation of internal and external classics, Buddhist relics, and field survey data, following the traditional cataloging method of seeking books based on categories and studying studies based on books. Jiedushi was not only the provincial governor during the middle and late Tang Dynasty, but also a synonym of a local administrative district. The predecessor of the Jiannan West Jiedushi, Jiannan Jiedushi, was one of the earliest Jiedushi established in the Tang Dynasty. Due to its developed economy and close proximity to the Guanzhong area, Jiannan West became an exceedingly important region of Tang Dynasty. Thus its significance was evident. At the same time, the flourishing of Buddhism in the Tang Dynasty reached its peak, affecting all fields. Under the influence of Buddhism, the bureaucrats and scholars generally worshipped Buddhism, among which included all the Jiannan West Jiedushi. In addition, under the bureaucratic system of Tang Dynasty, most Jiannan West Jiedushi were literary giants, which had significant influence on the formation and development of Chengdu's urban culture in the middle to late Tang Dynasty. Especially in religious activities, they extensively participated in the interaction between Confucianism and Buddhism, and treated famous monks with civility. And during their tenure, they either donated funds to build temples, or converted their residences into temples, or ordained people as monks. They fully supported the development of Buddhism, which not only united people in Jiannan West, but also indirectly stabilized the Tang Dynasty's rule of Jiannan West. This article comprehensively considers the background of the times, the intervention of political rights, the interaction of social classes, and the customs of life. At the same time, it refers to the influence of local officials represented by the Xichuan Jiedushi on religious philosophy, aesthetic psychology, cultural arts, sculpture, and other factors during this period, in order to objectively and comprehensively depict the Buddhism of Bashu in the middle and late Tang Dynasty.